Giant Condyloma Acuminata (Buschke-Lowenstein Tumor): Review of an Unusual Disease and Difficult to Manage - Jefferson F. Nieves-Condoy; Camilo L. Acuña-Pinzón; José L. Chavarría-Chavira; Diego Hinojosa-Ugarte; Luis A. Zúñiga-Vázquez (Hindawi Limited, 2021)
Giant condyloma acuminatum (GCA) or Buschke-Loewenstein tumor is a rare disease, with an estimated prevalence of 0.1%. It was initially described in 1896 by Buschke and later in 1925 by Buschke and Loewenstein. Classic condyloma acuminata (CCA) and squamous cell carcinoma (SCC) were initially described as different entities. These three entities are currently considered to correspond to the same spectrum of different but not exclusive malignant transformations, associated with multiple risk factors such infection by human papilloma virus (HPV), immunodeficiencies, poor hygiene, multiple sexual partners, and chronic genital infections. HPV subtypes 6 and 11 are associated with 90% of GCA. It presents as a cauliflower-like tumor in the genital region with bad odor, bleeding, and local infection, differential diagnosis with multiple conditions should be considered, and sexually transmitted diseases should always be investigated. GCA has a higher rate of malignant transformation than CCA and tends to infiltrate adjacent soft tissues. The therapeutic approach is controversial but is considered that the resection with free edges is the gold standard and can be combined with adjuncts. The recurrence rate is high. Overall mortality is 21% and is associated with morbidity caused by recurrences. Imiquimod cream 5% has recently shown good results as monotherapy and in combination with ablative and surgical treatments. The quality of life is diminished in patients with this condition. In this review, we address the different aspects of this rare entity including the therapeutic approach.